Element content analyses in the Institute for Food Sciences, Quality Assurance and Microbiology - Kovács, Béla; Andrási, Dávid; Fekete, István (Acta Agraria Debreceniensis, 2012)
The role of chemical elements to ensure and promote our health is undisputed. Some of them are essential for plants, animals and human, others can cause diseases. The major source of mineral constituents is food, drinking water has a minor contribution to it, so the knowledge of elemental intake through food is crucial and needs continuous monitoring and by this way it promotes the food quality assurance and dietetics. With the evolution of spectroscopic methods increasingly lower concentrations could be determined, so the elemental composition of a sample could be more precisely and fully described. Due to the results the gathered knowledge up to the present is supported and new observations can be done helping us to understand such complex systems as biological organisms are. The quality of a food is determined by the full process of its production, consequently it starts with agricultural production so elemental-analysis usually cover the whole soil – plant – (animal) – food chain, by this way the „Fork-to-Farm” precept is true in elemental analysis field also. The history of elemental analysis in the University of Debrecen, Centre for Agricultural and Applied Economic Sciences, Faculty of Agricultural and Food Sciences and Environmental Management, Institute of Food Processing, Quality Assurance and Microbiology goes back to 1980s when the so called Regional Measurement Central gave the background for research. The continuous deployment resulted in an obtain of an inductively coupled plasma atomic emission spectrometer (ICP-AES) in 1988, which extended the scope of examinations due to its excellent performance characteristics compared to flame atom absorption (FAAS) and flame emission spectrometers (FES). The instrumental park retain up to date correlate to the developing analytical techniques due to acquiring a newer ICPAES in 1998 and an inductively coupled plasma mass spectrometer in 2004 – which sensitivity is three order of magnitude better compared to ICP-AES. The Institute supports the work with its own ICP-AES and ICP-MS since 2011.